Enhancing the learning of fundamental football techniques: A Study on elementary school students - Muhammad Furqan; Meriza Faradilla; Khairul Rizal (Pelita International Publishing, 2024)
The objective of this study is to enhance the understanding of elementary school students at SDN Lamklat, Aceh Besar, regarding fundamental football techniques, including dribbling, kicking, and passing. A Classroom Action Research (CAR) approach was employed, conducted in two cycles comprising planning, implementation, observation, and reflection phases. The study involved 25 fourth-grade students as participants. Data were collected through skill tests, questionnaires, and observation sheets. The findings revealed a significant improvement in the mastery of basic football techniques. In the first cycle, 65% of students achieved satisfactory mastery with an average class score of 70. By the second cycle, 85% of students reached satisfactory mastery, with an average class score of 85. Practice- and game-based learning effectively boosted students' motivation and skills. Therefore, teaching fundamental football techniques using more interactive and contextual methods positively impacts student abilities. Similar methods are recommended to enhance skills in other sports disciplines.